Irrationality the enemy within - N. S Sutherland (London Constable, 1992)
Why do doctors, army generals, high-ranking government officials and other people in positions of power make bad decisions that cause harm to others? Why are punishments so ineffective? Why is interviewing such an unsatisfactory method of selection? Irrationality is a challenging and thought-provoking book that draws on statistical concepts, probability theory and a mass of intriguing research to expose the failings of human reasoning, judgment and intuition. The author explores the inconsistencies of human behavior, and discovers why even the experts find it so hard to make rational and unbiased decisions.
Includes index.
Keywords: Reasoning